(Anti)community as a category in the professional situation of lecturers at the university - Ewa Bochno (Studia z Teorii Wychowania)
The subject of this article is look at the university as an lecturers working space. There are two main aims. First, to indicate possibility of using metaphor in research. Secondly, in relation to the results of my own research on the professional functioning of young educators, to reveal perception of the everyday life of the university from their perspective.